Isolation and characterization of phytosteroid and Triterpenods from leaves of abutilon crispum - DR.M.RAM MOHAN; S.GANAPATY; B.VASUDHA (International Journal of Pharma and Bio Sciences, 2017)
Natural product have served as an important sources of drugs since ancient time and about half of the useful drugs today are derived from natural source. The study of natural products has advantage over synthetic drugs. Most of the phytochemical derived from natural source are extremely useful as lead structures for synthetic modifications and optimization of bioactivity. The aim of the study is to identify and characterize the bioactive compounds from leaves of Abutilon crispum. For isolation of the compounds, the dried leaves powder Abutilon crispum was subjected to extraction with chloroform and subject to column chromatography with different solvent fractions. Three compounds were isolated from the chloroform extract and purified. These compounds were eluted with benzene and petroleum ether. The structures of these compounds were characterized by using IR, NMR and Mass spectrometry. These compounds were isolated from this plant for the first time.